Pengaruh Performa Turbocharger Terhadap Kinerja Mesin Induk Di MT. Green Park - Sugeng Marsudi (Departemen Teknik Kelautan Universitas Hasanuddin, 2022)
The main propulsion engine (MPU), or the main motor on board, is a machine that functions to move the ship forward and backwards. The MPU has two combustion air intake systems in the cylinders, namely a suction intake system that relies on the vacuum of the combustion chamber due to piston movement or a press intake system, namely by equipping the engine with a Turbocharger. The primary purpose of a turbocharger is to increase the combustion air pressure by compressing the air so that the mass of air entering the combustion chamber becomes higher than atmospheric air. If the mass of the combustion air flow decreases due to various conditions, it will affect the incomplete combustion process, which can be visually indicated by darker smoke. Incomplete combustion will affect the power and performance of the diesel engine.